2013
DOI: 10.3390/ijms14035576
|View full text |Cite
|
Sign up to set email alerts
|

Naringin Enhances CaMKII Activity and Improves Long-Term Memory in a Mouse Model of Alzheimer’s Disease

Abstract: The Amyloid-β (Aβ)-induced impairment of hippocampal synaptic plasticity is an underlying mechanism of memory loss in the early stages of Alzheimer’s disease (AD) in human and mouse models. The inhibition of the calcium/calmodulin-dependent protein kinase II (CaMKII) autophosphorylation plays an important role in long-term memory. In this study, we isolated naringin from Pomelo peel (a Citrus species) and studied its effect on long-term memory in the APPswe/PS1dE9 transgenic mouse model of AD. Three-month-old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 35 publications
3
68
0
Order By: Relevance
“…Considering that naringin improves cognitive deficits in AD [14], we treated MHE rats with naringin (80 mg/kg). Naringin induced a significant increase in SA% in the YM compared with the MHE group (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that naringin improves cognitive deficits in AD [14], we treated MHE rats with naringin (80 mg/kg). Naringin induced a significant increase in SA% in the YM compared with the MHE group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported that the memory-improving effect of naringin on AD models is likely mediated either by enhancing the autophosphorylation of CaMKII, increasing the phosphorylation of the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic receptor at a CaMKII -dependent site [14], or by directly increasing GSK-3 β phosphorylation [25]. Additionally, our study observed that the JAK2/STAT3 axis is necessary for the pharmacological effect of naringin on MHE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NGN has well reported neuroprotective and memory enhancing effects [65,70,71]. NGN has proved to enhance long-term memory by enhancing activity of CAMII kinase [72], inhibiting NF-κB induced apoptosis [73] and decreasing cytokine release in vitro [74]. In the present study, MWM test was done to evaluate learning and memory deficits associated with COL-induced stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Aβ-induced synaptic deficits observed in CA1 hippocampal neurons are also dependent on the activation of NMDARs, but, in contrast, lead to the removal of AMPARs from the synapse (Mattson et al, 1992;Kim et al, 2001;Kamenetz et al, 2003b;Snyder et al, 2005;Tyszkiewicz and Yan, 2005;Hsieh et al, 2006b;Shankar et al, 2007;Parameshwaran et al, 2008;Li et al, 2009;Yamin, 2009;Cerpa et al, 2010;Decker et al, 2010;Kessels et al, 2010a;Ondrejcak et al, 2010;Klyubin et al, 2011;Rammes et al, 2011;Dinamarca et al, 2012;Ferreira et al, 2012;Kessels et al, 2013;Sivanesan et al, 2013;Tamburri et al, 2013). Additionally, the effects of Aβ involve decreased Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) activity (Gu et al, 2009;Zeng et al, 2010;Wang et al, 2013). Intriguingly, AD is accompanied with decreased levels of neurogranin in pyramidal neurons (Davidsson and Blennow, 1998).…”
Section: Accepted Manuscriptmentioning
confidence: 96%